Pesticide residue profiles, dietary risk assessment, and mitigation strategies in citrus production systems of Pakistan - Muneer Abbas; Akbar Hayat; Sohaib Afzaal; Muhammad Ghayoor Husnain; Hira Tariq; Fiaz Hussain; Niaz Hussain; Muhammad Saleem; Dilbar Hussain; Aleena Alam; Wang Dongze; Sohail Abbas (Food Control, 2026)

Understanding the heat stress mitigation mechanisms during pollen development in Gossypium hirsutum L. - Rabia Habib; Zulqurnain Khan; Abdel-Halim Ghazy; Shoaib ur Rehman; Kotb A. Attia; Maria Siddique; Sajid Fiaz; Abdullah A. Al-Doss; Muhammad Abu Bakar Saddique; Ummara Waheed (Molecular Biology Reports, 2026)

Multibiomarker assessment of greenly synthesized silver nanoparticles toxicity in the Tor putitora - Noman Waheed; Adeeba Naseer; Sabahat Saeed; Muhammad Fiaz Khan; Yukun Zhang; Venkata Siva Naga Sai Goli (Marine Pollution Bulletin, 2026)

A New Species of Coprinellus (Psathyrellaceae, Agaricales) From Buner District, Pakistan - Muhammad Ishaq; Sana; Muhammad Binyamin Khan; Munazza Kiran; Muhammad Fiaz; Abdul Nasir Khalid; Ting Chi Wen (New Zealand Journal of Botany, 2026)
A new species, Coprinellus nigrolamellatus , is described hereby from the Buner District, Khyber Pakhtunkhwa Province, Pakistan. The species is distinguished based on both morphological features and molecular data, with nrITS sequences confirming its unique status. Coprinellus nigrolamellatus is characterized by small‐ to medium‐sized basidiomata; an applanate and grayish‐brown pileus with yellowish orange central disk; adnexed, slowly deliquescent, and black lamellae; mitriform basidiospores (in front view) distinctly flattened (in side view) with a central germ pore; clavate to broadly clavate cheilocystidia; irregularly cylindrical pileocystidia; thick‐walled and globose to subcylindrical veil elements; and the absence of pleurocystidia. Phylogenetically, it forms a well‐supported sister clade to Coprinellus verrucispermus within section Coprinellus . Descriptions, illustrations, phylogenetic analysis results, and comparisons with closely related taxa are provided for the studied species.

Development and Performance Evaluation of an Indigenized Smart Field Lysimeter for Relative Crop Water-Use Assessment - Muhammad Faisal; Fiaz Hussain; Shoaib Rashid Saleem; Saliha Qamar (Water Conservation Science and Engineering, 2026)

Biochemical Characterization and Phylogenetic Diversity Assessment of Onion (Allium Cepa L.) Genotypes - Samira Habib; Syed Dilnawaz Ahmad Gardezi; Ahmed Mahmoud Ismail; Safira Attacha; Sajid Fiaz; Muhammad Imran Hamza; Armghan Shehzad; Shazia Arif (Plant Molecular Biology Reporter, 2026)

Retraction notice to ‘A facile two-step hydrothermal preparation of 2D/2D heterostructure of Bi2WO6/WS2 for the efficient photodegradation of blue under sunlight’ [Environ. Res. 234 (2023) 116550] - Muhammad Fiaz; Manzar Sohail; Ayman Nafady; Geoffrey Will; Md A. Wahab (Environmental Research, 2026)

Correction: Modulation of inflammatory and oxidative stress pathways by ethanolic extract of Suaeda fruticosa Forssk. Ex J.F.Gmel in animal models of ulcerative colitis - Juan Liu; Aqib Mustafa; Muhammad Fiaz; Hafiz Muhammad Zubair; Tahir Maqbool; Atiq ur Rehman; Muhammad Asif; Jing Yang (Inflammopharmacology, 2026)

Modulation of inflammatory and oxidative stress pathways by ethanolic extract of Suaeda fruticosa Forssk. Ex J.F.Gmel in animal models of ulcerative colitis - Juan Liu; Aqib Mustafa; Muhammad Fiaz; Hafiz Muhammad Zubair; Tahir Maqbool; Atiq ur Rehman; Muhammad Asif; Jing Yang (Inflammopharmacology, 2026)

Morphological Studies and Phylogenetic Analysis Unveil a New Species of Russula Subg. Heterophyllinae (Russulaceae, Russulales) from Pakistan - Muhammad Fiaz; Sana; Muhammad Binyamin Khan; Munazza Kiran; Muhammad Ishaq; Abdul Nasir Khalid; Ting Chi Wen (New Zealand Journal of Botany, 2026)
Russula subg. Heterophyllidiae is both ecologically and economically important. In the present study, a new Russula species, R . pakistanica , is described from Mansehra District, Khyber Pakhtunkhwa Province, Pakistan, based on morphology and molecular phylogenetic analyses of internal transcribed spacer (nrITS) region. Both morphological and phylogenetic analyses consistently confirmed that the species described belongs to Russula subg. Heterophyllidiae subsect. Virescentinae . Russula pakistanica is characterized by a concave, centrally depressed, striated, and light gray to cream yellow pileus; narrowly adnate and pale olive‐gray lamellae; clavate and very light gray to creamy buff stipe with bulbous base; broadly ellipsoid and partially reticulated basidiospores (average 8.5 × 6.6 μm); clavate to fusoid hymenial cystidia with obtuse apices; and the absence of marginal cells and pileocystidia. Phylogenetically, it formed a distinct and well‐supported sister clade to Chinese R . pallidula . The new species’ description, illustrations, phylogenetic analyses results, and comparison with closely related taxa are provided in this article.

Mixed convective heat transfer enhancement in hybrid nanofluid flow through complex-finned tube cavities - Noreen Sher Akbar; Salman Akhtar; Shakil Shaiq; Muhammad Fiaz Hussain; Taseer Muhammad; M. Farooq; M. Bilal Habib (Dynamics of Atmospheres and Oceans, 2025)

High accuracy computational approach to study Casson hybrid nanofluid flow under induced magnetic field inside wavy walls configuration having peristaltic motion with entropy generation - Noreen Sher Akbar; Javaria Akram; S. Ijaz; Zaib Jahan; Taseer Muhammad; Muhammad Bilal Habib; M. Fiaz Hussain; M. Farooq (Dynamics of Atmospheres and Oceans, 2025)

Prediction of RNA editing sites and genome-wide characterization and identification of PERK gene family in Oryza sativa in response to salinity stress - Hafiz Muhammad Waqas; Muhammad Abu Bakar Saddique; Sajid Fiaz; Afnan A. Alnufaei; Muhammad Ali Sher; Badr Alharthi; Muhammad Hammad Nadeem Tahir; Mahmood Alam Khan; Shahmeer Shahid; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2025)

Harnessing breeding and biotechnological innovations for global food security under climate change - Obaid Ur Rehman; Feifei Zhu; Xinjuan Hu; Xiangru Xu; Muhammad Uzair; Jiangya Qian; Sajid Fiaz; Shuhao Huo (Functional & Integrative Genomics, 2025)

Magnetic MOF-Based Immunosensing Strategy with Quantum Dot Labeling for Efficient Electro-chemiluminescent Detection of Alpha-fetoprotein - Mariyam Fatima; Muhammad Faizan; Iqra Jabeen; Muhammad Fiaz; Ansar Ali; Syed Kashif Ali; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Ibrahim Jafri; Abd-ElAziem Farouk (Journal of Fluorescence, 2025)

Comprehensive ampelographic and biochemical profiling of exotic grapevine (Vitis vinifera L.) cultivars grown under semi-arid conditions - Ubaid Abdul Khaliq; Irfan Ali; Abdel‑Halim Ghazy; Muhammad Tahir Akram; Mahmood-ul-Hassan; Haider Ali; Umer Habib; Tanveer Hussain; Kotb A. Attia; Sajid Fiaz; Abdullah A. Al-Doss; Muhammad Uzair; et al. (Genetic Resources and Crop Evolution, 2025)

Evaluating the impacts of environmental stresses on agriculture in the context of climate resilience - Muhammad Arif; Sajid Fiaz; W. M. W. W. Kandegama; Sujitraj Sheth; Luhua Li (Plant Molecular Biology, 2025)

Interactive Effects of Biochar Rates and Elevated Temperature on Organic Matter Cycling and Extracellular Enzyme Activity in a Sandy Loam Aridisol - Rummana Basit Mir; Muhammad Sanaullah; Faisal Mahmood; Sabir Hussain; Muhammad Hussnain Siddique; Hayssam M. Ali; Xingliang Xu; Afzal Ahmed; Umme-e-Aiman Fiaz; Tanvir Shahzad (Journal of Soil Science and Plant Nutrition, 2025)

Molecular phylogeny and cryptic species identification of the genus Triplophysa in the freshwater of Malakand division, Pakistan - Omer dad; Muhammad Fiaz Khan; Akhtar Rasool; Mohammad Attaullah; Muhammad Israr; Naveed Akhtar (Zoologischer Anzeiger, 2025)

Physio-biochemical and molecular mechanisms of low nitrogen stress tolerance in peanut (Arachis hypogaea L.) - Xiangjun Kong; Rui Wang; Peipei Jia; Hengbin Li; Aziz Khan; Ali Muhammad; Sajid Fiaz; Qunce Xing; Zhiyong Zhang (Plant Molecular Biology, 2025)

Exploring environmentally stable and novel genetic factors influencing rice grain shape and yield attributes - Sadia Gull; Zulqarnain Haider; Houwen Gu; Saleem Uddin; Muhammad Qasim; Rana Ahsan Raza Khan; Adil Altaf; Sajid Fiaz; Mona S. Alwahibi; Mohamed S. Elshikh; Rashid Iqbal; Jun Miao; et al. (Euphytica, 2025)

Down-regulation of interlinked inflammatory signalling cascades by ethanolic extract of Suaeda fruticosa Forssk. ex J.F. Gmel. attenuated in vivo inflammatory and nociceptive responses - Muhammad Fiaz; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Shafqat Rasul Chaudhry; Mohammad Saleem; Kashif ur Rehman Khan; Ashwaq Hamid Salem Yehya; Muhammad Asif (Inflammopharmacology, 2025)

Transcriptome-wide identification of microRNAs regulating plant immunity in Gossypium arboreum L. - Abdul Manan Khan; Muhammad Abu Bakar Saddique; Sajid Fiaz; Saba Zafar; Kotb A. Attia; Yaser M. Hafez; Arif Ahmed Mohammed (Genetic Resources and Crop Evolution, 2025)

Identification of novel antimicrobial compounds in colostrum-associated Lactiplantibacillus plantarum ZFS 1 and 2 by integrating in vitro, machine learning and bioinformatics approaches - Zainab Fiaz; Fatima Noor; Aqsa Ikram; Talha Ali Chohan; Muhammad Zubair Aslam; Najma Arshad (Food Bioscience, 2024)

An SNP based genotyping assay for genes associated with drought tolerance in bread wheat - Abdul Rauf; Muhammad Ali Sher; Umar Farooq; Awais Rasheed; Muhammad Sajjad; Ruilian Jing; Zulqurnain Khan; KOTB A. Attia; Arif Ahmed Mohammed; Sajid Fiaz; Jing Chen; Shoaib Ur Rehman (Molecular Biology Reports, 2024)

The comparative transcriptome analysis of two green super rice genotypes with varying tolerance to salt stress - Nageen Zahra; Muhammad Uzair; Imdad Ullah Zaid; Kotb A. Attia; Safeena Inam; Sajid Fiaz; Rizk M. Abdallah; Muhammad Kashif Naeem; Umer Farooq; Nazia Rehman; Ghulam Muhammad Ali; Jianlong Xu; et al. (Molecular Biology Reports, 2024)

Notes on species of Sporisorium and Ustilago from Pakistan - Sadiq Ullah; Najam-ul-Sehar Afshan; Aamna Ishaq; Maria Riaz; Muhammad Fiaz; Abdul Nasir Khalid; Mary Catherine Aime (Mycological Progress, 2024)

Performance evaluation of irrigation outlets with physical model study in Indus basin irrigation system of Pakistan - Ghulam Nabi; Fiaz Hussain; Bilal Sajjad; Muhammad Masood; Dengfeng Liu (Environmental Monitoring and Assessment, 2024)

Revealing the molecular mechanisms in wound healing and the effects of different physiological factors including diabetes, age, and stress - Muhammad Summer; Shaukat Ali; Umaima Fiaz; Tauqeer Hussain; Rana Rashad Mahmood Khan; Hashim Fiaz (Journal of Molecular Histology, 2024)

Identification, charectrization and genetic transformation of lignin and pectin polysaccharides through CRISPR/Cas9 in Nicotiana tobacum - Rana Imtiaz Ahmed; Angyan Ren; Dalal Sulaiman Alshaya; Sajid Fiaz; Yingzhen Kong; Shoaib Liaqat; Naushad Ali; Muhammad Abu Bakar Saddique; Kotb A. Attia; Mahmood Ul Hassan Taga (Functional & Integrative Genomics, 2024)

Prediction of RNA editing sites in maize under salt stress through transcriptomic approaches - Dalal Sulaiman Alshaya; Muhammad Uzair; Obaid Ur Rehman; Kotb A. Attia; M. H. Mubarak; Sajid Fiaz (Plant Biotechnology Reports, 2024)

Phytochemical profile, nutritional and medicinal value of Nigella sativa - Shabbir Hussain; Aqsa Rukhsar; Munawar Iqbal; Qurat ul Ain; Jahanzaib Fiaz; Noman Akhtar; Maria Afzal; Naveed Ahmad; Iqbal Ahmad; Wissem Mnif; Muhammad Hashir Khalid (Biocatalysis and Agricultural Biotechnology, 2024)

Molecular Characterization and Comparative Transcriptomic Analysis of Hr-Lcyb and Hr-Psy Genes for Carotenoids Synthesis in Sea Buckthorn (Hippophae rhamnoides L.) - Shazia Arif; Hafiz Muhammad Ahmed; Safira Attacha; Kotb A. Attia; Arif Ahmed Mohammed; Saira Ishaq; Shahid Iqbal Awan; Sajid Fiaz; Waseem Alam; Seung Hwan Yang (Journal of Soil Science and Plant Nutrition, 2024)

Phenotypic and Molecular Profiling of Vitis Vinifera L. Genotypes Against Anthracnose Through SCAR Markers - Qandeela Nigar; Mahmood ul Hassan; Rashid Mehmood Rana; Sadia Mehmood Satti; Summaira Ali; Muhammad Farhan Khan Pasha; Irfan Ali; Hafiz Muhamamd Ahmad; Sami Al Obaid; Mohammad Javed Ansari; Sajid Fiaz (Journal of Crop Health, 2024)

Launaea fragilis extract attenuated arthritis in rats through modulation of IL-1β, TNF-α, IL-6, NF-κB, COX-2, IL-4, and IL-10 - Muhammad Fiaz; Muhammad Asif; Kashif ur Rehman Khan (Inflammopharmacology, 2024)

Silicon nanoparticles: A novel approach in plant physiology to combat drought stress in arid environment - Muhammad Nazim; Xiangyi Li; Shazia Anjum; Fiaz Ahmad; Muqarrab Ali; Murad Muhammad; Khurram Shahzad; Lisha Lin; Usman Zulfiqar (Biocatalysis and Agricultural Biotechnology, 2024)

Characterization of the tubby-like proteins (TLPs) gene family in Cucumis sativus L.: insights into the evolution, structure, and expression patterns under salt stress - Ikram Ullah; Muhammad Uzair; Obaid Ur Rehman; Safira Attacha; Kotb A. Attia; Sheraz Ahmad; Muhammad Salman; Hamid Ali; Muhammad Abdul Rehman Rashid; Asmaa M. Abushady; Sajid Fiaz; Syed Jehangir Shah; et al. (Genetic Resources and Crop Evolution, 2024)

Harnessing probiotics and prebiotics as eco-friendly solution for cleaner shrimp aquaculture production: A state of the art scientific consensus - Muhammad Noman; Syed Shabi Ul Hassan Kazmi; Hafiz Sohaib Ahmed Saqib; Usama Fiaz; Paolo Pastorino; Damià Barcelò; Muhammad Tayyab; Wenhua Liu; Zhen Wang; Zaher Mundher Yaseen (Science of The Total Environment, 2024)

Genome-wide association study reveals novel genes on different chromosomal positions regulating boll weight in upland cotton (Gossypium hirsutum L.) - Zubair Iqbal; Muhammad Shahid Iqbal; Salman Alamery; Khurram Shehzad; Qamar U. Zaman; Safira Attacha; Zareen Sarfraz; Mian Faisal Nazir; Daowu Hu; Muhammad Mubashar Zafar; Aqib Zeb; Shoupuhe; et al. (Genetic Resources and Crop Evolution, 2024)

Impact of Various Combinations of Organic and Inorganic Fertilizers on Fruit Production and Quality of ‘Kinnow’ Mandarin (Citrus reticulata Blanco.) - Muhammad Asim; Faisal Hayat; Tehseen Ashraf; Fakhara Khanum; Juan Li; Yang Peng; Yanxiao Ma; Shahid Iqbal; Ummara Khan; Sitwat Riaz; Panfeng Tu; Fiaz Hussain; et al. (Applied Fruit Science, 2024)

Green synthesis of cobalt ferrite and Mn doped cobalt ferrite nanoparticles: Anticancer, antidiabetic and antibacterial studies - Sabahat Fiaz; Muhammad Naeem Ahmed; Ihsan ul Haq; Syed Wadood Ali Shah; Muhammad Waseem (Journal of Trace Elements in Medicine and Biology, 2023)

Comparative genomics of light harvesting chlorophyll (LHC) gene family and impact of chlorophyll-A contents under drought stress in Helianthus annuus - Parwsha Zaib; Hafiz Muhammad Ahmad; Safira Attacha; Mahmood-Ur Rahman; Muhammad Rizwan Shafiq; Kousar Parveen; Sajid Fiaz; Kotb A. Attia; Saira Ishaq; Shazia Arif; Asmaa M. Abushady; Muhammad Jawad Umer (Journal of Plant Physiology, 2023)

Genome-wide identification and expression analysis of U-box gene family in Juglans regia L. - Hanif Khan; Umar Zeb; Sadaf Gul; Azizullah Aziziullah; Naushad Ali; Sajid Fiaz; Asmaa M. Abushady; Shariat Ullah; Salar Muhammad; Kotb A. Attia; Itoh Kimiko; Fengjie Cui; et al. (Genetic Resources and Crop Evolution, 2023)

Genetic characterization of coarse and basmati rice (Oryza sativa L.) through microsatellite markers and morpho-agronomic traits - Tahira Luqman; Zia-ul Qamar; Aqsa Tabasum; Wael. H. El-Kallawy; Talha Nazir; Safira Attacha; Sajid Fiaz; Muhammad Azhar Nadeem; Amjad Hameed; Zahra Maryum; Itoh Kimiko; Kotb Attia (Genetic Resources and Crop Evolution, 2023)

Genome-wide characterization and expression analysis of cyclic nucleotide-gated ion channels (CNGCs) gene family in Arabidopsis thaliana L. and Helianthus annuus L. for drought stress - Sadaf Oranab; Hafiz Muhammad Ahmad; Sajid Fiaz; Athar Hussain; Muhammad Rizwan; Shazia Arif; Saira Ishaq; Shahnaz Zakia; Asmaa M. Abushady; Itoh Kimiko; Kotb A. Attia (Brazilian Journal of Botany, 2023)

An efficient virus-induced gene silencing of PDS gene in Solanum lycopersicum (cv. Rio Grande) and its functional analysis - Iqra Mehboob; Muhammad Mughees; Ayesha Baig; Shaukat Ali; Yasar Sajjad; Shahid Iqbal; Zahoor Hussain; Sajid Fiaz; Farhat Abbas; Kotb A. Attia; Asmaa M. Abushady; Mohammad Maroof Shah (Brazilian Journal of Botany, 2023)

RETRACTED: A facile two-step hydrothermal preparation of 2D/2D heterostructure of Bi2WO6/WS2 for the efficient photodegradation of methylene blue under sunlight - Muhammad Fiaz; Manzar Sohail; Ayman Nafady; Geoffrey Will; Md A. Wahab (Environmental Research, 2023)

Synergistic neuroprotection by phytocompounds of Bacopa monnieri in scopolamine-induced Alzheimer’s disease mice model - Shehla Shoukat; Muhammad Amir Zia; Muhammad Uzair; Roua A. Alsubki; Kaynat Sajid; Sana Shoukat; KOTB A. Attia; Sajid Fiaz; Shaukat Ali; Itoh Kimiko; Ghulam Muhammad Ali (Molecular Biology Reports, 2023)

Progress in genome-wide identification of RBPs and their role in mitigating stresses, and growth in plants - Muhammad Haroon; Hala Tariq; Rabail Afzal; Muhammad Anas; Shanza Nasar; Neha Kainat; Sajid Fiaz; Uswa Irfan; Fahad Idrees; Muhammad Mubashar Zafar (South African Journal of Botany, 2023)

Comprehensive insights into the regulatory mechanisms of lncRNA in alkaline-salt stress tolerance in rice - Obaid Ur Rehman; Muhammad Uzair; Muhammad Shahbaz Farooq; Bilal Saleem; Safira Attacha; Kotb A. Attia; Umer Farooq; Sajid Fiaz; Wael. H. El-Kallawy; Itoh Kimiko; Muhammad Ramzan Khan (Molecular Biology Reports, 2023)

Major challenges in widespread adaptation of aerobic rice system and potential opportunities for future sustainability - Muhammad Shahbaz Farooq; Hira Fatima; Obaid Ur Rehman; Muhammad Yousuf; Rabia Kalsoom; Sajid Fiaz; Muhammad Ramzan Khan; Muhammad Uzair; Shuhao Huo (South African Journal of Botany, 2023)

Therapeutic and immunomodulatory role of probiotics in breast cancer: A mechanistic review - Muhammad Summer; Shaukat Ali; Umaima Fiaz; Hafiz Muhammad Tahir; Muhammad Ijaz; Shumaila Mumtaz; Rabia Mushtaq; Rida Khan; Hafsa Shahzad; Hashim Fiaz (Archives of Microbiology, 2023)

Nitrogen Management Strategies to Improve Crop Performance, Recovery Efficiency and Their Relationship with Physiological Indices in Dry Direct-Seeded Rice - Hafeez ur Rehman; Imran Ali; Fiaz Ali; Masood Iqbal Awan; Abdul Wakeel; Muhammad Farooq; Mubshar Hussain (International Journal of Plant Production, 2023)

An overview of genome engineering in plants, including its scope, technologies, progress and grand challenges - Muhammad Sufyan; Umar Daraz; Sajjad Hyder; Usman Zulfiqar; Rashid Iqbal; Sayed M. Eldin; Farzana Rafiq; Naveed Mahmood; Khurram Shahzad; Muhammad Uzair; Sajid Fiaz; Iftikhar Ali (Functional & Integrative Genomics, 2023)

Antibiotics induced changes in nitrogen metabolism and antioxidative enzymes in mung bean (Vigna radiata) - Marium Fiaz; Iftikhar Ahmed; Sumara Masood Ul Hassan; Adnan Khan Niazi; Muhammad Fahim Khokhar; Zeshan; Muhammad Ansar Farooq; Muhammad Arshad (Science of The Total Environment, 2023)

The fungicide azoxystrobin causes histopathological and cytotoxic changes in the midgut of the honey bee Apis mellifera (Hymenoptera: Apidae) - Raissa Santana Serra; Luis Carlos Martínez; Jamile Fernanda Silva Cossolin; Matheus Tudor Candido Santos de Resende; Lenise Silva Carneiro; Muhammad Fiaz; Jose Eduardo Serrão (Ecotoxicology, 2023)

Application of silver nanoparticles synthesized through varying biogenic and chemical methods for wastewater treatment and health aspects - Asima Rasheed; Sabir Hussain; Waseem Mushtaq; Muhammad Zubair; Khadija Siddique; Kotb Attia; Naeem Khan; Sajid Fiaz; Farrukh Azeem; Yinglong Chen (Environmental Science and Pollution Research, 2023)

Effects of Mirabilis jalapa L. root extract and sildenafil on paroxetine-induced sexual dysfunction in male rats and characterization of its phytoconstituents by UPLC-MS - Asad Ur Rahman; Fiaz Alam; Zia Ur Rehman; Muhammad Khan; Tawseef Ahmad (South African Journal of Botany, 2023)

Analysis of Temperature Data Using the Innovative Trend Pivot Analysis Method and Trend Polygon Star Concept: A Case Study of Soan River Basin, Potohar, Pakistan - Fiaz Hussain; Ray-Shyan Wu; Ghulam Nabi; Rana Shahzad Noor; Muhammad Naveed Anjum; Muhammad Azam; Arslan Afzal (Pure and Applied Geophysics, 2023)
The trend analysis approach is used to estimate changing climate and its impact on the environment, agriculture and water resources. Innovative polygonal trend analyses are qualitative methods applied to detect changes in the environment. In this study, the Innovative Trend Pivot Analysis Method (ITPAM) and Trend Polygon Star Concept Method were applied for temperature trend detection in Soan River Basin (SRB), Potohar region, Pakistan. The average monthly temperature data (1995–2020) for 11 stations were used to create polygon graphics. Trend length and slope were calculated separately for arithmetic mean and standard deviation. The innovative methods produced useful scientific information, with the identification of monthly shifts and trend behaviors of temperature data at different stations. Some stations showed an increasing trend and others showed decreasing behavior. This increasing and decreasing variability is the result of climate change. The winter season temperature is increasing, and the months of December to February are getting warmer. Summer is expanding and pushing autumn towards winter, swallowing the early period of the cold season. The monthly polygonal trends with risk graphs depicted a clear picture of climate change in the Potohar region of Pakistan. The phenomena of observed average temperature changes, indicated by both qualitative methods, are interesting and have the potential to aid water managers’ understanding of the cropping system of the Potohar region.

MiRNA fine tuning for crop improvement: using advance computational models and biotechnological tools - Asad Abbas; Adnan Noor Shah; Mohsin Tanveer; Waseem Ahmed; Anis Ali Shah; Sajid Fiaz; Muhammad Mohsin Waqas; Sami Ullah (Molecular Biology Reports, 2022)

Molecular cloning, characterization and expression analysis of two 12-oxophytodienoate reductases (NtOPR1 and NtOPR2) from Nicotiana tabacum - Feiyan Huang; Farhat Abbas; Dylan O’Neill Rothenberg; Muhammad Imran; Sajid Fiaz; Naveed ur Rehman; Sikandar Amanullah; Afifa Younas; Yan Ding; Xianjie Cai; Xiaolong Chen; Lei Yu; et al. (Molecular Biology Reports, 2022)

Characterization of functional genes GS3 and GW2 and their effect on the grain size of various landraces of rice (Oryza sativa) - Haroon Rasheed; Sajid Fiaz; Muhammad Abid Khan; Sultan Mehmood; Faizan Ullah; Sumbul Saeed; Shahid Ullah Khan; Tabassam Yaseen; Reem M. Hussain; Abdul Qayyum (Molecular Biology Reports, 2022)

Comprehensive characterization of Guanosine monophosphate synthetase in Nicotiana tabacum - Feiyan Huang; Farhat Abbas; Sajid Fiaz; Muhammad Imran; Ke Yanguo; Waseem Hassan; Umair Ashraf; Yuansheng He; Xuanjie Cai; Zhijiang Wang; Lei Yu; Xianwen Ye; et al. (Molecular Biology Reports, 2022)

First report on molecular surveillance based on duplex detection of Anaplasma marginale and Theileria annulata in dairy cattle from Punjab, Pakistan - Farhan Ahmad Atif; Rao Zahid Abbas; Saba Mehnaz; Muhmmad Fiaz Qamar; Kashif Hussain; Muhammad Usman Nazir; Muhammad Arfan Zaman; Aman Ullah Khan; Mourad Ben Said (Tropical Animal Health and Production, 2022)

Biodiversity and ecological interactions of earthworm species from Poonch division Pakistan - Muhammad Umar Khan; Saiqa Andleeb; Muhammad Fiaz Khan; Rozina Ghulam Mustafa (Tropical Ecology, 2022)

Bio-diesel production of sunflower through sulphur management in a semi-arid subtropical environment - Athar Mahmood; Masood Iqbal Awan; Sana Sadaf; Ahmed Mukhtar; Xiukang Wang; Sajid Fiaz; Sher Aslam Khan; Habib Ali; Faran Muhammad; Zafar Hayat; Farhana Gul; Shah Fahad (Environmental Science and Pollution Research, 2022)

Analysis of food resources, host availability and insecticidal impacts on the fecundity, longevity and parasitism efficiency of Diaertiella rapae (M’intosh) - Ahmad Nawaz; Habib Ali; Sajid Fiaz; Muhammad Sufyan; Miza Abdul Qayyum; Rashid Azad; Yasir Niaz; Muhamamd Adnan Bodlah; Khalid Ali Khan (International Journal of Tropical Insect Science, 2021)

Prevalence of antibiotic-resistant bacterial strains in wastewater streams: molecular characterization and relative abundance - Marium Fiaz; Iftikhar Ahmed; Rabaila Riaz; Uzma Nawaz; Muhammad Arshad (Folia Microbiologica, 2021)

Appraisal of iron accumulation in soil, forages, and blood plasma of sheep and goats: a case study in different districts of Punjab, Pakistan - Zafar Iqbal Khan; Kafeel Ahmad; Samra Siddique; Kinza Wajid; Humayun Bashir; Muhammad Nadeem; Muhammad Fiaz Qamar; Muhammad Fahad Ullah; Saif Ur Rehman (Environmental Science and Pollution Research, 2021)

Identification of GH17 gene family in Vitis vinifera and expression analysis of GH17 under various adversities - Tariq Pervaiz; Tianhua Liu; Xiang Fang; Yanhua Ren; Xiyang Li; Zhongjie Liu; Muhammad Fiaz; Jinggui Fang; Lingfei Shangguan (Physiology and Molecular Biology of Plants, 2021)

In Vitro Studies for the Evaluation of Insecticidal Potential of the Venom of Endoparasitic Wasp Aenasius arizonensis (Girault) (Hymenoptera, Encyrtidae) - Saqi Kosar Abbas; Zain Ul Abdin; Muhammad Arshad; Fiaz Hussain; Amer Jamil (International Journal of Peptide Research and Therapeutics, 2021)

Morphology and composition of the midgut bacterial community of Scaptocoris castanea Perty, 1830 (Hemiptera: Cydnidae) - Jamile Fernanda Silva Cossolin; Déborah Romaskevis Gomes Lopes; Luis Carlos Martínez; Helen Cristina Pinto Santos; Muhammad Fiaz; Mônica Josene Barbosa Pereira; Lucia Madalena Vivan; Hilário Cuquetto Mantovani; José Eduardo Serrão (Cell and Tissue Research, 2020)

Future Vision for Autonomous Ocean Observations - Christopher Whitt; Jay Pearlman; Brian Polagye; Frank Caimi; Frank Muller-Karger; Andrea Copping; Heather Spence; Shyam Madhusudhana; William Kirkwood; Ludovic Grosjean; Bilal Muhammad Fiaz; Satinder Singh; et al. (Frontiers in Marine Science, 2020)

Cytotoxicity of Piper aduncum (Piperaceae) essential oil in brown stink bug Euschistus heros (Heteroptera: Pentatomidae) - Jamile F. S. Cossolin; Mônica J. B. Pereira; Luis C. Martínez; Leonardo M. Turchen; Muhammad Fiaz; Hakan Bozdoğan; José Eduardo Serrão (Ecotoxicology, 2019)

Input Selection of Wavelet-Coupled Neural Network Models for Rainfall-Runoff Modelling - Muhammad Shoaib; Asaad Y. Shamseldin; Sher Khan; Muhammad Sultan; Fiaz Ahmad; Tahir Sultan; Zakir Hussain Dahri; Irfan Ali (Water Resources Management, 2019)

Genetic characterization of phenicol-resistant Escherichia coli and role of wild-type repressor/regulator gene (acrR) on phenicol resistance - Muhammad Yaqoob; Li Ping Wang; Jam Kashif; Javed Memon; Sajid Umar; Muhammad Farooq Iqbal; Muhammad Fiaz; Cheng-Ping Lu (Folia Microbiologica, 2018)

Impact of drought on assimilates partitioning associated fruiting physiognomies and yield quality attributes of desert grown cotton - Muhammad Shareef; Dongwei Gui; Fanjiang Zeng; Zeeshan Ahmed; Muhammad Waqas; Bo Zhang; Hassan Iqbal; Muhammad Fiaz (Acta Physiologiae Plantarum, 2018)

Inferring the contribution of sexual reproduction, migration and off‐season survival to the temporal maintenance of microbial populations: a case study on the wheat fungal pathogen P uccinia striiformis f.sp. tritici - Sajid Ali; Pierre Gladieux; Hidayatur Rahman; Muhammad S. Saqib; Muhammad Fiaz; Habib Ahmad; Marc Leconte; Angélique Gautier; Annemarie F. Justesen; Mogens S. Hovmøller; Jérôme Enjalbert; Claude de Vallavieille‐Pope (Molecular Ecology, 2014)
Understanding the mode of temporal maintenance of plant pathogens is an important domain of microbial ecology research. Due to the inconspicuous nature of microbes, their temporal maintenance cannot be studied directly through tracking individuals and their progeny. Here, we suggest a series of population genetic analyses on molecular marker variation in temporally spaced samples to infer about the relative contribution of sexual reproduction, off‐season survival and migration to the temporal maintenance of pathogen populations. We used the proposed approach to investigate the temporal maintenance of wheat yellow rust pathogen, P uccinia striiformis f.sp. tritici ( PST ), in the H imalayan region of P akistan. Multilocus microsatellite genotyping of PST isolates revealed high genotypic diversity and recombinant population structure across all locations, confirming the existence of sexual reproduction in this region. The genotypes were assigned to four genetic groups, revealing a clear differentiation between zones with and without B erberis spp., the alternate host of PST , with an additional subdivision within the B erberis zone. The lack of any differentiation between samples across two sampling years, and the very infrequent resampling of multilocus genotypes over years at a given location was consistent with limited over‐year clonal survival, and a limited genetic drift. The off‐season oversummering population in the B erberis zone, likely to be maintained locally, served as a source of migrants contributing to the temporal maintenance in the non‐ B erberis zone. Our study hence demonstrated the contribution of both sexual recombination and off‐season oversummering survival to the temporal maintenance of the pathogen. These new insights into the population biology of PST highlight the general usefulness of the analytical approach proposed.

Erratum to: Effect of varying dietary energy levels during the last trimester of pregnancy on subsequent first lactation performance in Sahiwal heifers - Muhammad Fiaz; Muhammad Abdullah; Muhammad Nasir; Khalid Javed; Masroor Ellahi Babar; Talat Naseer Pasha; Makhdoom Abdul Jabbar (Tropical Animal Health and Production, 2014)

Effect of varying dietary energy levels during the last trimester of pregnancy on subsequent first lactation performance in Sahiwal heifers - Muhammad Fiaz; Muhammad Abdullah; Muhammad Nasir; Khalid Javed; Masroor Ellahi Babar; Talat Naseer Pasha; Makhdoom Abdul Jabbar (Tropical Animal Health and Production, 2012)